Calcaneus stress fracture: a case report - M. Rodrigues, Sonia; Marques, Raquel P.; Teixeira, Ricardo C.; Chaves, Pedro; Rodrigues, Catarina; Valverde, Amilcar (International Journal of Research in Orthopaedics, 2024)
Calcaneal stress fracture is a rare clinical entity associated with diverse etiological factors such as high intensity training, female sex, smoking and poor nutrition. The authors present a case of a calcaneal stress fracture treated conservatively with immobilization, limited weight bearing and vitamin D supplementation.